DISCOLORATION OF NANOHYBRID AND NANOFILLER RESIN COMPOSITES AFTER EXPOSURE TO TURMERIC - Yasmin Safira Virgiani; Adioro Soetojo; Nanik zubaidah (Universitas Airlangga, 2021)
Background: Recently, the demand of aesthetic restorative has greatly increased and enchourages the development of composite resin material. The latest technology of composite is nanohybrid and nanofiller composites. However, color stability of nanohybrid and nanofiller resin composites can be influence by intrinscic and (or) extrinsic factor. Intrinsic factor depends on the composition on the resin composite and extrinsic factor such as colored food and beverages. Turmeric as a food ingredients, that is often consumed by Indonesians can cause discoloration in composites, because it contains the active pigment curcuminoid. The discoloration of nanohybrid and nanofilles composites can caused by the process of water sorbstion and curcumin particles. Purpose: Explain the discoloration of nanohybrid and nanofiller resin composites after exposure to turmeric and the factor that influence. Review(s): The reaction between the curcumin contained in turmeric and nanohybrid as well as nanofiller composites can cause discoloration in both composites. One of the reasons behind the discoloration on composite resin is that the composite resin can absorb water and its substances are carried by the water. Discoloration of composites was influence by the concentration of turmeric solution, pH of the solution, finishing and polishing process, temperature, time of exposure, composition of filler and matrix. Conclusion: Turmeric as an extrinsic factor can cause color changes in nanohybrid and nanofiller composites (ΔE>3,3), where the level of color change can be obtained by intrinsic factors, such as composition of filler and matrix, and other extrinsic factors.